2004
DOI: 10.1128/mcb.24.13.5923-5936.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Myc E-Box Phylogenetic Footprints in Glycolytic Genes by Chromatin Immunoprecipitation Assays

Abstract: Prediction of gene regulatory sequences using phylogenetic footprinting has advanced considerably but lacks experimental validation. Here, we report whether transcription factor binding sites predicted by dot plotting or web-based Trafac analysis could be validated by chromatin immunoprecipitation assays. MYC overexpression enhances glycolysis without hypoxia and hence may contribute to altered tumor metabolism. Because the full spectrum of glycolytic genes directly regulated by Myc is not known, we chose Myc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
249
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(273 citation statements)
references
References 48 publications
23
249
0
1
Order By: Relevance
“…We found substantially increased glycolysis in premalignant B lineage-committed Eμ-myc bone marrow cells, consistent with the increased size of these cells and analyses of cell lines showing that c-Myc directly binds regulatory elements in the chromatin of genes encoding glycolytic enzymes to increase their expression (35). Of note, we found that PARP14 is crucial for Eμ-myc cells fully to increase their glycolysis and size.…”
Section: Discussionsupporting
confidence: 66%
“…We found substantially increased glycolysis in premalignant B lineage-committed Eμ-myc bone marrow cells, consistent with the increased size of these cells and analyses of cell lines showing that c-Myc directly binds regulatory elements in the chromatin of genes encoding glycolytic enzymes to increase their expression (35). Of note, we found that PARP14 is crucial for Eμ-myc cells fully to increase their glycolysis and size.…”
Section: Discussionsupporting
confidence: 66%
“…MYC activates glycolysis through transcriptional induction of various glycolytic enzymes and LDH-A (Shim et al, 1997;Kim et al, 2004). Recent experiments using double transgenic mice expressing c-MYC in a doxycycline-dependent manner specifically in hepatocytes revealed that overexpression of a multitude of glycolysis genes in tumors was abrogated by switching off c-MYC expression .…”
Section: The Metabolic Pattern Of Cancer Cellsmentioning
confidence: 99%
“…37 Additionally, activated Akt inhibits the TSC1/TSC2, which in turn inhibits ras homolog enriched in brain leading to increased mTOR signaling. Increased mTOR activity enhances transcription of glycolytic enzymes, 38,39 protein synthesis through S6K and 4EBP1 phosphorylation, and cell growth. 29 In addition to augmenting glycolysis, Akt promotes increased fatty acid synthesis by phosphorylating and activating ATP citrate lyase 40 and as a secondary consequence of increased flux through glycolysis, nucleic acid synthesis is enhanced through ribose production from the pentose phosphate pathway.…”
Section: Ampk Activation In Cancer Cellsmentioning
confidence: 99%